RESPON MASYARAKAT TERHADAP PENANGAN KASUS KEKERASAN TERHADAP PEREMPUAN DI PALANGKA RAYA - Evi Nurleni; Riamona S. Tulis (Prodi Sosiologi FISIP UPR, 2022)
Based on the year- end report of the Women and Children Empowerment Agency or BPPA in 2014, there were 13 cases of violence against women and 21 cases of violence against children. Violence against women occurred in the general group of 25 years and over as many as 12 people, and all of them were married as many as 12 people, with a college education level, 6 cases, high school 6 cases and the remaining 2 people at the elementary and junior high school levels 2 people, 5 of whom are civil servants and the rest are civil servants' wives. This study raises 2 questions, namely what are the procedures for handling cases and victims of violence against women at P2TP2A BPPA and PPA POLRES Palangka Raya? How is the response of the Mandawai Community of Palangka Raya City to the handling of cases and victims of violence against women and children in the city of Palangka Raya? Furthermore, using a gender framework analysis to analyze the data. Based on the research results, domestic violence is only considered serious if the victim has experienced physical violence and the incident has occurred repeatedly. Sexual and verbal violence in society is rarely considered as part of a form of violence that should be resolved in the legal realm, and is not even considered violence. Based on the above understanding, the handling of cases of domestic violence is that women are in a subordinate position, where there is an unequal power relationship between men and women. The husband is the holder of control over finances or income and decisions in the household. So in the case of domestic violence, there is a possibility that women's basic practical needs are not met or there is neglect. Women become parties who are obliged to accept the treatment or control of men, because it is culturally like that and the wife or woman has an obligation to maintain the integrity of her household. Women are the minimal party in mastering their own strategic basic needs. Because a woman's body is not something that is neutral, but has been